Prelaryngeal and/or pretracheal lymph node metastasis could help to identify papillary thyroid carcinoma with intermediate risk from unilateral lobe cT1-2N0 papillary thyroid carcinoma - Wang, Bin; Zhu, Chun-Rong; Fei, Yuan; Liu, Hong; Yao, Xin-Min; Wu, Jian (Frontiers in Endocrinology, 2023)
Objective: The study aims to explore the possibility of prelaryngeal and/or pretracheal lymph node metastasis in identifying papillary thyroid carcinoma with more than 5 metastatic central lymph nodes from unilateral lobe cT1-2N0 papillary thyroid carcinoma. Methods: A retrospective analysis was conducted on patients who underwent the initial thyroid surgery for unilateral lobe cT1-2N0 PTC in a single tertiary center between July 2018 to December 2022. Multivariable binary logistic regression analysis was used to identify risk factors for unilateral lobe cT1-2N0 papillary thyroid carcinoma with more than 5 metastatic central lymph nodes. Results: A total of 737 patients were included in the study and 399 patients were confirmed to suffer from occult central lymph node metastasis. The larger size of the largest diameter of tumor (> 1cm; OR = 3.3, 95%CI 1.6 – 6.83; p = 0.001), pretracheal lymph node metastasis (OR = 5.91, 95%CI 2.73 – 12.77; p < 0.001), prelaryngeal lymph node metastasis (OR = 3.74, 95%CI 1.73 – 8.1; p = 0.001), ipsilateral paratracheal lymph node metastasis (OR = 12.22, 95%CI 3.43 – 43.48; p < 0.001), and contralateral paratracheal lymph node metastasis (OR = 7.68, 95%CI 3.86 – 15.3; p < 0.001) were confirmed to be risk factors for unilateral lobe cT1-2N0 PTC with more than 5 metastatic central lymph nodes. When more than two metastatic prelaryngeal and/or pretracheal lymph nodes occurred, the incidence of more than 5 metastatic central lymph nodes was 71.2%. Conclusion: Prelaryngeal and/or pretracheal lymph node metastasis could help to identify papillary thyroid carcinoma with more than 5 metastatic central lymph nodes from unilateral lobe cT1-2N0 papillary thyroid carcinoma. When more than two metastatic pretracheal and/or prelaryngeal lymph nodes occurred, total thyroidectomy and ipsilateral central lymph node dissection should be performed and contralateral paratracheal lymph node dissection might be also necessary.